2018
DOI: 10.3390/en11092230
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Effects of Baffles with Various Thermal and Geometrical Conditions on Thermo-Fluid Dynamics and Kinetic Power of a Solar Updraft Tower

Abstract: Solar updraft towers (SUTs) are used for renewable power generation, taking advantage of the thermal updraft air flow caused by solar energy. Aerodynamic devices have been applied to SUTs to improve their performance and the baffle is one such device. Here, we investigate the effect of baffle installation on the thermo-fluid dynamic phenomena in the collector of an SUT and how it enhances the overall SUT performance using computational fluid dynamics analysis. Two geometric parameters (height and width of baff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In our previous studies on the height and location of baffles, baffles have been shown to play an active role in the transfer of heat accumulated in the absorber to the air flow in the SUT. In a study of baffle height, the positive and negative effects of the baffle within the SUT was investigated, and performance improvement of up to 4.69% was confirmed [9]. The baffle location influences flow, which is divided into circulating flow and main flow in the collector, and it was confirmed that the baffle located at the inlet of the collector contributes the most toward enhancing the performance of the SUT [10].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our previous studies on the height and location of baffles, baffles have been shown to play an active role in the transfer of heat accumulated in the absorber to the air flow in the SUT. In a study of baffle height, the positive and negative effects of the baffle within the SUT was investigated, and performance improvement of up to 4.69% was confirmed [9]. The baffle location influences flow, which is divided into circulating flow and main flow in the collector, and it was confirmed that the baffle located at the inlet of the collector contributes the most toward enhancing the performance of the SUT [10].…”
Section: Introductionmentioning
confidence: 89%
“…As one of the aims of this study was to quantify the interactions between the CGP and the baffle, we further created models with both the CGP and baffle installed in the collector. In the case of the baffle, the optimal shape, size, and installation location values determined in our previous studies [9,10] were used-0.15 m high, 0.08 m wide, and location of r = 4.5 m (from the center). As mentioned above, depending on the 15 geometries of the CGP and existence of a baffle, a total of thirty models were analyzed in this study (fifteen models for analyzing the effect of the CGP, and an additional fifteen models for investigating the simultaneous effects of the CGP and baffle).…”
Section: Computational Models and Boundary Conditionsmentioning
confidence: 99%
“…The geometry of the SUT analyzed in this study is basically the same as two previous studies of the SUT with the baffle mentioned above [13,14]. The total height of the SUT is 13 m, the chimney height is 12 m, the collector diameter is 10 m, the inlet of the collector has a height of 0.15 m, and the chimney diameter is 0.25 m (Figure 2a).…”
Section: Geometrymentioning
confidence: 99%
“…The chimney, roof, and baffle are assumed to be adiabatic ( Table 2). The abovementioned boundary conditions refer to our previous model study [14]. The reason for setting the chimney and roof to the adiabatic condition is to assume no heat loss for that part.…”
Section: Computational Models and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation